Highly sensitive detection of small ruminant bovine spongiform encephalopathy within transmissible spongiform encephalopathy mixes by serial protein misfolding cyclic amplification - Gough, Kevin C.; Bishop, Keith; Maddison, Ben C. (American Society for Microbiology, 2014)
It is assumed that sheep and goats consumed the same bovine spongiform encephalopathy (BSE)-contaminated meat and bone meal that was fed to cattle and precipitated the BSE epidemic in the United Kingdom that peaked more than 20 years ago. De- spite intensive surveillance for cases of BSE within the small ruminant populations of the United Kingdom and European Union, no instances of BSE have been detected in sheep, and in only two instances has BSE been discovered in goats. If BSE is present within the small ruminant populations, it may be at subclinical levels, may manifest as scrapie, or may be masked by coinfection with scrapie. To determine whether BSE is potentially circulating at low levels within the European small ruminant populations, highly sensitive assays that can specifically detect BSE, even within the presence of scrapie prion protein, are required. Here, we present a novel assay based on the specific amplification of BSE PrPSc using the serial protein misfolding cyclic amplification as- say (sPMCA), which specifically amplified small amounts of ovine and caprine BSE agent which had been mixed into a range of scrapie-positive brain homogenates. We detected the BSE prion protein within a large excess of classical, atypical, and CH1641 scrapie isolates. In a blind trial, this sPMCA-based assay specifically amplified BSE PrPSc within brain mixes with 100% specific- ity and 97% sensitivity when BSE agent was diluted into scrapie-infected brain homogenates at 1% (vol/vol).